Do senescent cells in vivo induce a bystander effect in muscle? - Silva, Paulo Francisco Lopes da (2016)
SILVA, Paulo Francisco Lopes da - Do senescent cells in vivo induce a bystander effect in muscle?. Coimbra : [s.n.], 2016. Dissertação de Mestrado.